Desenvolvimento e caracterização de vitrocerâmicas com nanopartículas de titanatos de cálcio e bário - Silveira, Wagner da (2021)
Functional vitreous and glass-ceramic materials have been extensively studied in recent decades due to their interesting characteristics, which can be exploited in various applications, such as waterproof coatings, smart windows and even bioglass. Based on this range of applications and knowing that there is still room for the development of novel functional materials, this work proposes the development of glass-ceramics by the fusion process, in which dispersed phases of BaTiO3, CaTiO3 and BaTiO3-CaTiO3 can be nucleated in a matrix SiO2 base. The manufacturing process involved the mixing and fusion of precursor oxides (SiO2, TiO2, Al2O3) and carbonates (CaCO3, BaCO3) in alumina crucibles. Then, with the molten material, frits and glass-ceramic plates were obtained, which were characterized by X-Ray Diffractometry (DRX), Differential Thermal Analysis (DTA), X-Ray Fluorescence Spectrometry (FRX), X-Ray Dispersion Spectroscopy in Energy (EDS), micro-Raman, Scanning Electron Microscopy (SEM) and Optical Microscopy, impedance and hardness analysis. Through DTA, it was possible to determine the crystallization temperatures of the proposed glass ceramics: 960ºC for the Ca-Si and Ba-Si sample, 1000 ºC for the BaCa-Si sample and 1120ºC for the Ba-Si sample. To evaluate the crystallization process in these temperature ranges, heat treatments of 30 min, 2h, 4h and 6h were used. Through structure refinement by the Rietveld method, it was possible to obtain the percentage of crystallized phases. For the Ba-Si glass-ceramic with heat treatment for 6 hours (1120ºC) the final microstructure was BaTiO3 (68.07%) Ba2TiSi2O8 (19.82%) and Ba2SiO4 (12.11%). For the Ca-Si glass-ceramic with heat treatment for 6 hours (1120ºC) the final microstructure was CaTiO3 (79.21%), CaTiSiO5 (11.25%) and Ca8Si5O18 (9.54%). For the BaCa-Si glass-ceramic it was not possible to carry out the structure refinement, but the presence of the following phases of interest was observed: BaTiO3, CaTiO3 and BaCaTiO4. The Vickers hardness test was performed to identify the hardness of the glass-ceramic samples, with the highest hardness value being observed for the Ca-Si glass-ceramic (831HV) and the lowest value for the Ba-Si glass-ceramic (486HV). Electrical measurements showed how capacitance variation can be correlated with heat treatment time. In general, the results show that it is possible to obtain glass ceramics with dispersed phases of BaTiO3 and/or CaTiO3, and that their properties can be modified by heat treatment.